Relationship between force parameters and performance in 100m front crawl swimming - Rozi, G.; Thanopoulos, V.; Dopsaj, M. (Sport Science - International Scientific Journal of Kinesiology, 2018)
Strength in water has been evaluated in several ways. The most common method is tethered swimming, a valid and reliable source of information for freestyle sprint swimmers. Yeater et al., (1981) concluded that tethered swimming method can provide prediction of performance as well as diagnose of technical problems. The aim of the research is to investigate the relationship between the 100 m freestyle swimming and the variables that determine force application during freestyle sprint swimming. In this study 23 active swimmers of national level participated (age = 15,04±1,6 years, body height =169,7±8,7 cm and body mass=62,4±9,7kg ).Firstly, force of the right handgrip was recorded with a portable dynamometer. After a warm up, participants was asked to swim with maximum intensity fully tethered with freestyle their best time of 100m freestyle swimming. For the determination of the relationship between the independent and the dependent variable, stepwise multivariate regression analysis will be applied. Two prediction models occurred from the analysis. The variables that best describe the criterion variable are circumference of biceps in contraction and mean force. The finding of this research confirms that tethered swimming is a useful tool for the coaches and swimmers in order to reach best results.